Higher Prevalence of Bacteroides fragilis in Crohn’s Disease Exacerbations and Strain-Dependent Increase of Epithelial Resistance - Becker, Heike E. F.; Jamin, Casper; Bervoets, Liene; Boleij, Annemarie; Xu, Pan; Pierik, Marie J.; Stassen, Frank R. M.; Savelkoul, Paul H. M.; Penders, John; Jonkers, Daisy M. A. E. (Frontiers in Microbiology, 2021)
Bacteroides fragilis has previously been linked to Crohn’s disease (CD) exacerbations, but results are inconsistent and underlying mechanisms unknown. This study investigates the epidemiology of B. fragilis and its virulence factors bft (enterotoxin) and ubiquitin among 181 CD patients and the impact on the intestinal epithelial barrier in vitro. The prevalence of B. fragilis was significantly higher in active (n=69/88, 78.4%) as compared to remissive (n=58/93, 62.4%, p=0.018) CD patients. Moreover, B. fragilis was associated with intestinal strictures. Interestingly, the intestinal barrier function, as examined by transepithelial electrical resistance (TEER) measurements of Caco-2 monolayers, increased when exposed to secretomes of bft-positive (bft-1 and bft-2 isotype; increased TEER ~160%, p<0.001) but not when exposed to bft-negative strains. Whole metagenome sequencing and metabolomics, respectively, identified nine coding sequences and two metabolites that discriminated TEER-increasing from non-TEER-increasing strains. This study revealed a higher B. fragilis prevalence during exacerbation. Surprisingly, bft-positive secretomes increased epithelial resistance, but we excluded Bft as the likely causative factor.